Santa Buddies : the legend of Santa Paws - McRoberts, Anna.; Vince, Robert; Lloyd, Christopher, 1938-; Woodburn, Danny, 1964-; Wendt, George; Flitter, Josh.; Panitz, Ty.; Gordon, Zachary, 1998-; Heit, Jonathan Morgan; Lord, Quinn; Cate, Field, 1997-; Wenger, Brahm; et al. (Burbank, Calif. : Distributed by Walt Disney Studios Home Entertainment, 2009)
When Puppy Paws, the fun-loving son of Santa Paws, gets tired of the North Pole, he finds Budderball on Santa's naughty list and figures he's just the dog to show him how to be an ordinary pup. But when the magical Christmas Icicle starts to melt and the world begins to forget the true meaning of the season, it's up to Puppy Paws and his newfound Buddies to save Christmas.
Title from container.
Widescreen.
Special features: Sing-along to A Christmas Carol with the Buddies; all-new music video.
Director of photography, Kamal Derkaoui ; music, Brahm Wenger.
Christopher Lloyd, Danny Woodburn, George Wendt.
Voices: Josh Flitter, Ty Panitz, Zachary Gordon, Jonathan Morgan Heit, Quinn Lord, Field Cate.
Keywords: Puppies -- Juvenile drama; Santa Claus -- Juvenile drama; North Pole -- Juvenile drama; Christmas films; Fantasy films; Children's films; Feature films; Films for the hearing impaired